2011
DOI: 10.1007/s10157-011-0440-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of acute kidney injury post-cardiopulmonary bypass in children

Abstract: AKI is common and occurred in 11% of our patients following CPB; however, AKI requiring renal replacement therapy is uncommon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
51
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 28 publications
7
51
1
2
Order By: Relevance
“…9,10 Similarly early recovery and less likelihood of progression to CKD has also been reported in earlier studies. [9][10][11]17,21 We found prolonged CPB time to be associated with higher odds of developing AKI which was consistent with previous studies. [9][10][11]21,22 The possible reason of longer CPB time associated with AKI is multifactorial and probably due to the physiological alternation occurring during CPB.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…9,10 Similarly early recovery and less likelihood of progression to CKD has also been reported in earlier studies. [9][10][11]17,21 We found prolonged CPB time to be associated with higher odds of developing AKI which was consistent with previous studies. [9][10][11]21,22 The possible reason of longer CPB time associated with AKI is multifactorial and probably due to the physiological alternation occurring during CPB.…”
Section: Discussionsupporting
confidence: 82%
“…Low cardiac output and sepsis has also been associated with AKI in previous reports. 17,21 The current study shows a significant increase in mortality in patients with stage 2 and 3 AKI compared to those without. Similarly significantly higher requirement of prolonged ventilation and length of ICU stay was found in children with stage 2 and 3 AKI compared to those without.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…2,[5][6][7]18,19,20,22,23 Sethi et al reported that duration of CPB >90 minutes could cause AKI in adults. 24 Similarly, Zheng et al reported that AKI was significantly more common in patients with duration of CPB >90 minutes. 20 Although the mechanism is unknown, the release of proinflammatory mediators, coagulation products, oxidation products, and the adhesion of blood cells to the vascular endothelium reportedly increases with prolonged CPb time.…”
Section: Discussionmentioning
confidence: 95%
“…In recent years, there has been growing interest to elucidate the risk factors for AKI in infants undergoing cardiothoracic procedures with CPB. Five factors have been shown to predict AKI including younger age, weight <10 kg, myocardial dysfunction, sepsis, and duration of CPB >90 min [ 286 ]. Another study reported multiple perioperative risk factors for acute kidney risk or injury, failure, and mortality in children undergoing CPB [ 290 ].…”
Section: Renal and Gastrointestinal Effectsmentioning
confidence: 97%